Estudio de la funcionalidad de los canales de irrigación en Caray y su continuidad en el valle de Virú - Ruiz Salazar, Cynthia Madeleini (2023)
After centuries of abandonment of hydraulic management with canals in the Viru basin, there is an academic initiative to investigate the continuity and use of pre-Hispanic canals; The objective of this thesis is to specify the study of irrigation channels in Caray, their functionality and continuity in the Virú valley. The research is basic with a causal correlational non-experimental design, and we worked with two variables, making use of the empirical-analytical scientific method, and the ethnographic method, having as an important tool the direct observation of the architectural evidence, the work of collecting information with the irrigation commission and the population involved in the recovery and use of the canals. The methodology that was applied was divided into field work and office work. The field work was carried out by prospecting and traversing all the channels, making a detailed record of each one of them. allowed to define the materials, the construction technique and current use of said pre-Hispanic canals. In the office work, the information was processed, the records, graphics, photographs and how much material was made in the field was analyzed and drawings were made. In both activities it was complemented with bibliographic information The results obtained from the investigation in the village of Caray, in the middle valley of Virú, indicate that the canals were built with the masonry technique, and they used flagstone with a mud coating; stacked stone technique (pirca) as lining and support of channel profiles; technique of the blocks carved in the rock and with masonry; mixed technique, built with drywall and undermined in the earth, and reconstructed channels used PVC. Of the nine registered canals, six have been reconstructed (canal 2,3,5, 7, 8 and 9). At present, all of them continue to function and carry water to the fields of the farmers of the Caray hamlet, and to ensure the frequent operation of Said channels, the users board is in charge of coordinating the maintenance every six months, and certifying the equitable distribution of the water quota to each one of the users. In this same sense, the watchdog entity for the ideal development of said user boards is the National Water Authority (ANA).